Komunikasi Persuasif Pedagang Online Terhadap Perubahan Kebiasaan Berbelanja Pada Masyarakat Sumbawa - Eka Khusnul Amalia; Ofi Hidayat (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2023)
The research aims to understand the persuasive communication used by online traders as the cause of changing online shopping habits. This research uses a qualitative descriptive research approach. Data collection techniques using interviews, observations and documentation. Information is determined based on purposive sampling techniques. Case studies in the study include online shop DS Kuline, Yumna Official, and HUG Florist & Furniture Store. The results of the research showed that online salespeople's communication process using the persuasive communication strategy they implemented can influence prospective buyers to conduct online transactions, according to the Computer Mediated Communication (CMC) Theory, which contains six dimensions: accessibility (range), speed (information speed), amount (information quantity), cognitive effectiveness (effectiveness), relevance (information suitability), and motivating dimensions. The theory of Computer Mediated Communication (CMC) is quite effective in influencing consumers in online transactions.